Networked psychostimulants: a web-based ethnographic study. Issue 1 (22nd January 2020) - Robitaille, Caroline
Abstract : Purpose: The purpose of this paper is to understand contemporary psychostimulant use among members of online discussion fora. Two objectives are addressed: to describe accounts of practices related to psychostimulant use, and to examine how these pharmaceuticals may shape contemporary subjectivities. Design/methodology/approach: This paper presents a qualitative analysis of three online discussion fora belonging to Reddit. Drawing on actor-network theory, psychostimulants are envisaged as networked actants to understand the underlying logics related to their use. Non-participant observation of r/Adderall was carried out over an 18-month period. A qualitative analysis of postings on the three selected fora was also performed. Findings: For each discussion forum, a network comprised of human and non-human actors was observed: members of the forum, psychostimulants as objects and subreddits as agentic spaces. This study reveals the emergence of multiple subjectivities associated with psychostimulant use: productivity, wellness and enhancement‐related. Practical implications: Findings open to a wider debate regarding public health's and healthcare professionals' understanding of psychostimulant use outside of the clinical setting and how this may contrast with how psychostimulant use is practiced in context. Originality/value: This research shows new online socio-cultural spaces formed around psychostimulant use. Calling upon a web-based ethnographic approach, this research presents a new perspective on the contemporary use of psychostimulants.